The dark side of empathy in narcissistic personality disorder - di Giacomo, Ester; Andreini, Elena; Lorusso, Ottavia; Clerici, Massimo (Frontiers in Psychiatry, 2023)
Narcissistic personality disorder is characterized by self-absorption, grandiosity, exploitation of others and lack of empathy. People with that disorder may switch from an overt form, mainly with grandiosity, to a covert presentation, with fears, hypersensitivity and dependence from others. Empathy represents a key point in detecting people affected by narcissistic personality disorder because, even if it is described as reduced, it plays a fundamental role in exploitation and manipulation. A systematic search of Literature without any language or time restriction, was performed combining thesaurus and free-search indexing terms related to Narcissistic personality disorder and empathy and produced 531 results. Fifty-two papers that analyzed possible issues in the empathic attitude of people with narcissistic personality disorder were included in this narrative review. Empathy is the capability of understating and feeling others emotions. It is not a unitary construct and can be distinguished in cognitive and affective. It might be channeled into prosocial and antisocial behaviors. A crucial trait identified in narcissistic empathy is affective dissonance that is closely related to rivalry as part of the dark tetrad (narcissism, machiavellianism, psychopathy, and sadism). Subjects affected by narcissistic personality disorder show greater impairment in affective aspects while their cognitive part of empathy appears preserved. Saving at least the cognitive aspects of empathy may contribute to therapeutic improvement of affective aspects.